2021
DOI: 10.1080/1331677x.2021.1926304
|View full text |Cite
|
Sign up to set email alerts
|

The monetary policy during shocks: an analysis of large Asian economies’ response to COVID-19

Abstract: The economies all over the world that have been adversely affected by the COVID-19 pandemic have recently started to devise different strategies to mitigate its consequences. Therefore, in order to dwell deeper into the measures taken by the policy makers around the world, this paper specifically analyzes how the monetary policies have been devised, in response to COVID-19. For this purpose, this paper has taken into consideration a panel of 8 Asian economies that have been affected the most acutely by the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Macroeconomic changes during the COVID-19 pandemic have been analyzed in some papers, but not on a cross-country-income level. Authors in [ 41 ] have used the Phillips curve in an Auto-Regressive Distributed Lag (ARDL) model to find the effect of shocks caused by lockdowns on the monetary policies, and the economy’s response to the affected policies. They concluded that to reduce the negative impacts of the COVID-19 pandemic on the economy, countries are taking less prudent monetary policies compared to before.…”
Section: Introductionmentioning
confidence: 99%
“…Macroeconomic changes during the COVID-19 pandemic have been analyzed in some papers, but not on a cross-country-income level. Authors in [ 41 ] have used the Phillips curve in an Auto-Regressive Distributed Lag (ARDL) model to find the effect of shocks caused by lockdowns on the monetary policies, and the economy’s response to the affected policies. They concluded that to reduce the negative impacts of the COVID-19 pandemic on the economy, countries are taking less prudent monetary policies compared to before.…”
Section: Introductionmentioning
confidence: 99%
“…Xt represents contemporaneous, while X(t-1) shows each variable's instantaneous behavior in this model specification. The detailed derivations of such models can be found in VAR literature (Bernanke & Mihov, 1998;Shahab & Mahmood, 2012;Ma et al, 2022).…”
Section: Model and Methodologymentioning
confidence: 99%
“…For instance, drought-induced food price spikes may create an impression of structural livelihood changes among food system actors when no such changes have occurred. To address such endogeneity, we used a reduced-form pooled-panel equation model (Ash et al 2020;Dang and Trinh 2022;Hovhannisyan et al 2020;Ma et al 2022). The reduced-form panel model expresses the effects of anticontagion COVID-19 policies on aggregate food system actor's livelihood outcomes, y, in the data (here, y refers to food security, food expenditure, food expenditure share, and income), making it possible to disentangle the simultaneous effects of the demand and supply forces on the livelihood outcomes.…”
Section: Panel Analytical Framework For Livelihood and Spatial-econom...mentioning
confidence: 99%